2004
DOI: 10.1159/000077753
|View full text |Cite
|
Sign up to set email alerts
|

Changing Paradigms in Concepts on Dental Caries: Consequences for Oral Health Care

Abstract: Kuhn proposed in his Structure of Scientific Revolutions (1962) that the theoretical framework of a science (paradigm) determines how each generation of researchers construes a causal sequence. Paradigm change is infrequent and revolutionary; thereafter previous knowledge and ideas become partially redundant. This paper discusses two paradigms central to cariology. The first concerns the most successful caries-preventive agent: fluoride. When it was thought that fluoride had to be present during tooth minerali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
409
0
132

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 606 publications
(548 citation statements)
references
References 57 publications
7
409
0
132
Order By: Relevance
“…The most remarkable data on the relationship between dietary sugars and caries in man come from the meticulous sequential studies in Japan (15)(16)(17)(18)(19)(20) where it became clear that the dose-response relationship is log-linear or arithmetically curvilinear even though the diagnostic level of caries used was cavitation; a late stage of caries (39) . There is no evident threshold for sugars below which there are no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The most remarkable data on the relationship between dietary sugars and caries in man come from the meticulous sequential studies in Japan (15)(16)(17)(18)(19)(20) where it became clear that the dose-response relationship is log-linear or arithmetically curvilinear even though the diagnostic level of caries used was cavitation; a late stage of caries (39) . There is no evident threshold for sugars below which there are no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, without targeting and reducing dental plaque, fluoride products are unable to completely inhibit dental caries (Fejerskov 2004). Natural products and derivatives, such as green tea catechins (Hirasawa et al 2006), cranberry constituents , Galla chinensis (Xie et al 2008), citrus lemon oil (Liu et al 2013), mushroom extracts (Yano et al 2010), and several bioactive macromolecules (Shang et al 2014;Lee and Park 2015), have been reported to be effective against the growth and adherence of S. mutans.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Dental caries is a multifactorial disease defined as a result of loss of mineral leading to dissolution of dental hard tissues by substantial pH fluctuations within the biofilm on the tooth surface (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%